PERTANGGUNG JAWABAN PIDANA PENGEMIS YANG DILAKUKAN MELALUI LIVE STREAMING TIKTOK: Criminal Liability for Begging Conducted Through TikTok Live Streaming - Nurma Novita Sari; Yudha Bagus Tunggala Putra (CLEAR: Criminal Law Review, 2024)
The phenomenon of begging is not only occurring in public spaces; with the advancement of technology, this phenomenon has also emerged in the virtual world, particularly on TikTok, where individuals engage in inappropriate methods to gain the sympathy of others and receive gifts that can be  exchanged for money. This practice is referred to as online begging. The rise of online beggars can be attributed to several factors, including a lack of education, limited skills, and the influence of the surrounding environment.Among these, the lack of education and skills is the primary reason why some individuals choose to become beggars. Education is a critical factor in determining one's wage value and plays a significant role in influencing income levels within society. As such, education serves as a benchmark for acquiring employment status. Based on the background regarding the phenomenon outlined above, this thesis focuses on the following research questions: 1) Can online beggars, using electronic media platforms (such aslive streaming on TikTok), be prosecuted under Article 504 of the Indonesian Penal Code (KUHP)? 2) What is the Islamic legal perspective on the phenomenon of online begging through electronic media (such as live streaming on TikTok)?